(3JMaI GdcQGe aj JGQjN ecI hGdeSLO GdMQGes - (3GdnqWnHGnWnHGFj GdHQhLQOj, GHf GdeQJVi, HMQ GdYdhe, eMeO egOj Hf eQJVi Hf eMeO, J (B1212 (3g`s ((3YHGS Hf Ydj cGTa GdZWGAs)
(3ChdgG (B:s
(3GdMeO ddg hGdUdGI Ydi eMeO hBdg, Gddge Hc CSJYjf hHCUajGFc CJhSd hCJTaYs
(3BNQgG (B:s
(3hCjVG bhdg JYGdi(B: (3hJbdHc aj GdSGLOjf, Ydi CMO GdJaGSjQ Cf GdeQGO ef SGLO Edi SGLO(B. (3GfJgi ef GdHNGQjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B7(3, U(B113s
(3GdCYdGe(B: (3L(B7(3, U(B113s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJGQjNs